Barriers to Household Risk Management : Evidence from India - Cole, Shawn; Giné, Xavier; Tobacman, Jeremy; Topalova, Petia; Townsend, Robert; Vickery, James (2012)
Why do many households remain exposed to large exogenous sources of non-systematic income risk? This paper uses a series of randomized field experiments in rural India to test the importance of price and non-price factors in the adoption of an innovative rainfall insurance product. The analysis finds that demand is significantly price-elastic, but that even if insurance were offered with payout ratios similar to US, widespread coverage would not be achieved. The paper identifies key non-price frictions that limit demand: liquidity constraints, particularly among poor households, lack of trust, and limited salience. The authors suggest potential improvements in contract design to mitigate these frictions.